Le développement de filières locales est-il gage d’une écologisation des pratiques agricoles ? - Hélène Brives; Claire Heinisch; Mathieu Désolé; Carole Chazoule; Perrine Vandenbroucke (Développement Durable et Territoires)
According to the literature on short local food systems, the direct relationship between consumers and producers triggers a virtuous circle that relies upon shared trust. What happens when the relationship is no longer direct but mediated by a small number of intermediaries? Socio-technical processes of changing agricultural practices are questionned by analysing the emergence of two local food chains in the Auvergne Rhône Alpes region: local soybean and minced steaks. Enrollment in a local food chain does not necessarily imply that producers adopt more agro-ecological practices. Nonetheless practices considered as environmental friendly are valued by local food chains. Sociotechnical objects or food chain governance have the potential to question farmers practices and invite to move the focus on long term learning processes.